Novel Nanostructured Polymeric Carriers to Enable Drug Delivery for Cardiovascular Diseases - O. Morales, Javier; Sepulveda-Rivas, Sabrina; Oyarzun-Ampuero, Felipe; Lavandero, Sergio; J. Kogan, Marcelo (Current Pharmaceutical Design, 2015)
Applications of polymeric nanotechnologies for enabling therapies for cardiovascular diseases have shown recent success. Both intravenous and oral administration have been investigated and achieved different degrees of development. While circulating polymeric nanostructured carriers are subjected to a number of interactions, smart nanoparticle design has enabled the formulation of active molecules to be delivered to specific targets for cardiovascular effects. This review aims at outlining the multiple factors that can affect the fate of polymeric nanostructured carriers in systemic circulation. With an understanding of these factors, the literature on the various polymeric nanostructured carriers is reviewed. Finally, the emerging uses of nanotechnology to formulate orally administered drugs for cardiovascular diseases are depicted.
Keywords: polymeric nanoparticles